Direct ink writing for electroresponsive human machine interfaces - Pethe, Shreyas Dinesh (Nanyang Technological University, 2021)
To aid with efficient and reliable communication with machines, Human-Machine Interfaces (HMIs) are crucial. Current approaches for HMIs rely on rigid, non-compliant devices. This structural non-compliance with inherently soft, curvilinear human body makes interfaces non-intuitive and limits widespread applications of HMIs. Hence, it is necessary to develop newer, compliant form factors for HMIs via development of soft sensors and responsive devices. Existing methods for fabrication of soft devices require high temperature processing and are hence not suitable for large scale devices made with soft polymeric materials. Extrusion based additive manufacturing methods such as Direct Ink Writing (DIW) show great potential for this application. This work focuses on optimization and modification of DIW system to handle various viscosities of inks, and special functional materials, to fabricate all-printed HMI devices. Initially, a custom DIW setup was assembled in-house. 3 axis motion stage was used for moving the dispensing head. Syringe pump and peristaltic pumps were used for low viscosity inks. Pneumatic ink dispenser was used for highly viscous shear thinning inks. The Syringe-pump system was modified to accommodate Phase Change Material (PCM) ink for tactile response devices. Formulations of various composite material systems were optimized for printing via DIW systems. First, a low viscosity conducting ink of PEDOT:PSS and MWCNT aqueous suspensions was prepared. 2 different dilutions of MWCNT, 0.5mg/ml and 1mg/ml were prepared and mixed with PEDOT:PSS in varying volume ratios. 1:3 ratio of PEDOT:PSS to 0.5 mg/ml MWCNT suspension was found out to have lowest resistivity. Subsequently, Acetylene black nanoparticles were mixed with PDMS to form viscous conducting composite ink. Percolation threshold for the network is found out to be at ~13%(w/w). To maintain printability, loading was limited to 15% and ink was prepared by adding crosslinker and thinner to the mixture. Further, Polyethylene glycol (PEG) was dispensed using a modified setup to keep it molten. Ti3C2 MXene was intercalated using LiBr and DMSO and delaminated to prepare 10mg/ml suspension which was added to PEG. The PEG-MXene composite had higher amount of nucleation sites. This helped in speeding up the phase transformation of printed patterns. For the sensing part of HMI, various tactile sensors were printed using the developed conducting inks. PEDOT:PSS-MWCNT composite was used to fabricate bending angle sensor, and strain sensor. The bending angle sensor shows fast, highly linear response with up to 10° resolution, and a rage of 0-180°. The strain sensor successfully measures small strains with ΔR/R0=15 measured for 5% strain. Further, Acetylene black – PDMS ink was utilized for fabrication of proximity sensor. Material differentiation and water content detection using these sensors is demonstrated. Different sensor geometries were tested and upto 2% of ΔC/C0 was achieved for metallic object. PEG-MXene PCM ink was used along with silver joule heater to fabricate flexible hardness modulation based tactile response devices. A thermally modulated transition resulting in 10 times change in hardness of the material was obtained as a response. A 3*3 array of such devices was printed to demonstrate display of letters via hardness modulation Finally, future scope of this project is discussed. Challenges for printing inks such as MXene dispersions and Liquid Metal are presented. Results of initial experiments carried out for newer printing paradigms such as 3D printing of stretchable materials and multimaterial printing is discussed. Further, newer devices such as all printed stretchable electroluminescent devices and printed active devices such as TFTs are proposed.